(untitled) (Comillas Journal of International Relations, 2023)
One of the factor that helps explain the ongoing conflict between Ukraine and Russia, is religion. Aplying five modes in which the social sciences reference religion (identity, culture, relations, practice and power) this article analyses the religious dimensions of the conflict by exploring historical and current aspects. We cannot affirm that the conflict is a religious conflict, yet, without taking into account the religious dimensions of both nations’ social and political life, we cannot fully grasp its nature.